2017
DOI: 10.1158/1055-9965.epi-16-0800
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Patients Having False-Positive Multitarget Stool DNA Tests after Negative Screening Colonoscopy: The LONG-HAUL Cohort Study

Abstract: Background Studies of colorectal cancer (CRC) screening by multi-target stool DNA (MT-sDNA) show false positive (FP) rates of 7–13%. It is unclear whether FP patients are at increased long-term risk of adverse outcomes. Methods We compared subsequent clinical events among patients with apparent FP MT-sDNA to those in patients reported as true negative (TN). This was a retrospective cohort study of participants in pre-FDA approval MT-sDNA studies having non-advanced or negative baseline colonoscopy findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Patients with positive mt‐sDNA results and a negative follow‐up colonoscopy may undergo more aggressive short‐term surveillance because of heightened concerns related to unresolved false‐positive findings. In 2 follow‐up studies of patients with false‐positive results on mt‐sDNA with median follow‐up of approximately 4 years, no excess rates of CRC or aero‐digestive malignancies were identified . In a more recent study by Cooper et al that included follow‐up mt‐sDNA, colonoscopy and upper endoscopy among 12 patients who had prior positive mt‐sDNA results and a negative colonoscopy, 7 patients had negative stool tests and colonoscopies, whereas 3 among the remaining 5 patients had positive findings on their follow‐up colonoscopy (2 advanced and 1 nonadvanced adenoma) .…”
Section: Options For Crc Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with positive mt‐sDNA results and a negative follow‐up colonoscopy may undergo more aggressive short‐term surveillance because of heightened concerns related to unresolved false‐positive findings. In 2 follow‐up studies of patients with false‐positive results on mt‐sDNA with median follow‐up of approximately 4 years, no excess rates of CRC or aero‐digestive malignancies were identified . In a more recent study by Cooper et al that included follow‐up mt‐sDNA, colonoscopy and upper endoscopy among 12 patients who had prior positive mt‐sDNA results and a negative colonoscopy, 7 patients had negative stool tests and colonoscopies, whereas 3 among the remaining 5 patients had positive findings on their follow‐up colonoscopy (2 advanced and 1 nonadvanced adenoma) .…”
Section: Options For Crc Screeningmentioning
confidence: 99%
“…In 2 follow-up studies of patients with false-positive results on mt-sDNA with median follow-up of approximately 4 years, no excess rates of CRC or aero-digestive malignancies were identified. 122,123 In a more recent study by Cooper et al that included follow-up mt-sDNA, colonoscopy and upper endoscopy among 12 patients who had prior positive mt-sDNA results and a negative colonoscopy, 7 patients had negative stool tests and colonoscopies, whereas 3 among the remaining 5 patients had positive findings on their follow-up colonoscopy (2 advanced and 1 nonadvanced adenoma). 124 Longer term follow-up will be required to provide greater reassurance and guide management, but the findings from Cooper et al are a reminder that high-quality colonoscopy is critically important, especially in the proximal colon, when following up positive findings on an mt-sDNA test.…”
Section: Stool-based Crc Screening Testsmentioning
confidence: 99%
“…However, concerns have been raised about the situation in which an mt‐sDNA test is positive and colonoscopy is negative, based on the assumption that a test that is sensitive for exfoliated DNA may have detected an indication of cancer in another organ. Whereas the few follow‐up studies that have been undertaken have not identified any excess non‐CRC cancer rate or excess mortality, more reassuring evidence about unresolved positive test results comes from a recent study by Cooper et al, who retested 12 patients with prior positive mt‐sDNA and negative colonoscopy results 11 to 29 months after the initial test. During reexamination, 7 patients had negative stool tests and colonoscopy; among the remaining 5 patients, 3 had positive findings on their follow‐up colonoscopy (2 advanced adenomas and 1 nonadvanced adenoma), suggesting that the initial follow‐up colonoscopies were false‐negative findings …”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, it is known that colonoscopy is an imperfect “gold standard”, with a quoted miss rate for advanced adenomas of up to 11% (3) and 2.6%–9.0% of cancers developing within 3 years of colonoscopy (interval cancers) (4). While neoplasms in the upper gastrointestinal tract or pancreas (5) are known to produce genetic markers that may survive passage into the stool and be detectable in stool assays, a recently published cohort study that followed more than 1000 patients with a false positive sDNA test found only 8 subsequent cancers (3 lung, 3 pancreas, 1 colon, 1 biliary) at an average 4 year follow up, which was not greater than expected in the general population (6). A similarly low estimate of extracolonic sources of sDNA test positivity was found in a case-control study (2 positive aerodigestive cancers for each 10,000 patients screened) (7).…”
Section: Introductionmentioning
confidence: 99%